A mathematical model for motions of gyroscope suspended from flexible cord. Issue 1 (31st December 2016) - Usubamatov, Ryspek
Abstract: Gyroscope devices are primary units for navigation and control systems in aviation and space engineering. The main property of the gyroscope is maintaining the axis of a spinning rotor, based on the principles of the angular momentum of the spinning rotor. However, the nature of the gyroscope's acting forces and motions is more complex. The torque applied to the gyroscope generates the internal resistance and precession torques based on acting simultaneously and interdependently, namely, centrifugal, common inertial and Coriolis forces generated by the mass elements of the spinning rotor as well as changes in angular momentum. This system of internal torques based on new fundamental principles of the gyroscope theory that enabled deriving the mathematical model for the motions of a gyroscope suspended from the flexible cord, which was a most unsolvable problem. The test results of the gyroscope motions well validated the new analytical approach.